ENHANCEMENT OF FUMARIC ACID PRODUCTION BY RHYZOPUS ORYZAE USING OXYGEN - VECTOR - CIOBANU, Corina; TUCALIUC, Alexandra; CRISTINA BLAGA, Alexandra; GALACTION, Anca-Irina; CAȘCAVAL, Dan (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Fumaric acid, one of the most important organic acids with various applications in industries, can be obtained by fungal fermentation processes, mainly by using Rhizopus oryzae as producing microorganism. The challenges are to maintain pellet morphology of fungy and to optimize the multiple factors that influence fumaric acid production. The main objective of this study is to improve fumaric acid production by varying n-dodecane concentration levels in batch fungal fermentations. This strategy leads to an increase of fumaric acid concentration for about 1.2 times in system with 5% n-dodecane but a higher hydrocarbon concentration induced inhibition phenomenon to fumaric acid production.